2006
DOI: 10.1007/s10641-006-9143-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of leptocephali of the freshwater eels, genus Anguilla, in the waters off west Sumatra in the Indian Ocean

Abstract: A research cruise was conducted in the eastern Indian Ocean off west Sumatra, Indonesia, in June 2003 to learn about the spawning and larval ecology of the tropical freshwater eels of the genus Anguilla in the region. A total of 43 anguillid leptocephali were collected during the cruise and they were genetically identified as 41 Anguilla bicolor bicolor, 1 Anguilla marmorata, and 1 Anguilla interioris. A. bicolor bicolor leptocephali were 44.1-55.5 mm TL and most of them were at the fully grown stage. Reexamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 20 publications
5
41
0
4
Order By: Relevance
“…Japanese scientists then discovered the spawning area of A. japonica in 1991 (Tsukamoto 1992) after smaller and smaller larvae were collected farther offshore . These surveys expanded out across the Indo-Pacific (Aoyama et al 2003(Aoyama et al , 2007Kuroki et al 2006) with evidence of offshore spawning by eels in the western South Pacific being found (Kuroki et al 2008;Aoyama 2009) and local spawning by eels in the Indonesian seas being discovered (Aoyama et al 2003). These collections and genetic or morphological information about anguillid population structures (Minegishi et al 2008;Watanabe et al 2008Watanabe et al , 2011 and silver eel tagging studies (Schabetsberger et al 2015;Jellyman and Tsukamoto 2010) led to ideas about the locations of Indo-Pacific anguillid spawning areas ( Fig.…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 99%
See 2 more Smart Citations
“…Japanese scientists then discovered the spawning area of A. japonica in 1991 (Tsukamoto 1992) after smaller and smaller larvae were collected farther offshore . These surveys expanded out across the Indo-Pacific (Aoyama et al 2003(Aoyama et al , 2007Kuroki et al 2006) with evidence of offshore spawning by eels in the western South Pacific being found (Kuroki et al 2008;Aoyama 2009) and local spawning by eels in the Indonesian seas being discovered (Aoyama et al 2003). These collections and genetic or morphological information about anguillid population structures (Minegishi et al 2008;Watanabe et al 2008Watanabe et al , 2011 and silver eel tagging studies (Schabetsberger et al 2015;Jellyman and Tsukamoto 2010) led to ideas about the locations of Indo-Pacific anguillid spawning areas ( Fig.…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 99%
“…None of the surveys had sampling stations distributed with appropriate geographic coverage to be able to understand the larval dispersal patterns of each species, but they showed that anguillid leptocephali are widely distributed in the deepwater areas of the region. Anguilla bicolor bicolor leptocephali were abundant off West Sumatra in SeptemberNovember 1929, however (Jespersen 1942), and were present in June 2003 (Aoyama et al 2007), indicating spawning occurs in that area. It is unclear though how widely the larvae from that spawning area may be dispersed by the South Equatorial Current or by equatorial jets (Fig.…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 99%
See 1 more Smart Citation
“…Spawning seasons of temperate anguillids have been roughly estimated from the timing of the downstream migrations of silver eels into the ocean (Jellyman 2003;Tesch 2003) Kleckner and McCleave 1988;Tsukamoto 1992;Tsukamoto et al 2003). The timing of spawning of tropical anguillids is much less understood, however, even though seasonal differences have been observed in the presence or size of leptocephali in the central Indonesian Seas (Wouthuyzen et al 2009) and off west Sumatra in the eastern Indian Ocean (Jespersen 1942;Aoyama et al 2007).…”
Section: -4 Seasonal Occurrence Of Leptocephalimentioning
confidence: 99%
“…Sampling at each station consisted of two tows of an Isaacs-Kidd midwater trawl (IKMT) with a mouth opening or 8.7 m 2 and a 0.5-mm mesh size. At each station, the IKMT was deployed at night in an oblique tow and a step tow (five horizontal sampling layers), both of which sampled the upper 200 m (see Aoyama et al 2007 andMiller et al 2011a for details). An extra tow was made at stn.…”
Section: Methodsmentioning
confidence: 99%